Geochemical Characterization of Zircon in Fyfe Hills of the Napier Complex, East Antarctica - Mami Takehara; Kenji Horie; Tomokazu Hokada (Minerals, 2020)
Ultra-high temperature (UHT) metamorphism plays an essential role in the development and stabilization of continents through accretionary and collisional orogenesis. The Napier Complex, East Antarctica, preserves UHT metamorphism, and the timing is still debated. U–Pb zircon geochronology integrated with rare earth element (REE) and oxygen isotope was applied to a garnet-bearing quartzo-feldspathic gneiss to confirm the timing of UHT metamorphism in Fyfe Hills in the western part of the Napier Complex. The zircons are analyzed using a sensitive high-resolution ion microprobe (SHRIMP). The cathodoluminescence observation and U–Pb ages allowed us to classify the analytical domains into three types: inherited domains (Group I), metamorphic domains (Group II), and U–Pb system disturbed domains (Group III). The REE patterns of Group II are characterized by a weak fractionation between the middle REE and heavy REE, which reinforces the above classification. The 207Pb*/206Pb* ages of Group II have an age peak at 2501 Ma, therefore, the gneiss experienced high temperature metamorphism at 2501 Ma. δ18O of zircons are homogeneous among the three groups (5.53 ± 0.11‰, 5.51 ± 0.14‰, and 5.53 ± 0.23‰), which suggests re-equilibration of oxygen isotopes after metamorphism at ca. 2501Ma under dry UHT conditions.